The Changing of Islamic education curriculum Paradigm in Public Universities - Yusuf Hanafi (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
Since the reformation era, the curriculum of Islamic Education in public universities has gone through such three modifications as Islamic education curriculum of 2000, 2002, and 2013. The objective of this research is to analyze the construction of the three kinds of the curriculum as well as the changing of the paradigm related to them comparatively. The paradigm of Islamic education curriculum 2000 was the continuity of the curriculum in the New Order era which was purely oriented to normative Islamic concepts (aqidah, syari’at, akhlak). In the opposite, Curriculum 2002 indicated many changes in its paradigm and material. Religion was not only a set of norms, but it also existed in reality and it was dynamic in responding the development of human being. Meanwhile, curriculum 2013 tried to emphasize the scientific learning approach by activating the students in building their knowledge. In other words, the learning activity is activity base-oriented, not content base-oriented.